Beta-propeller protein-associated neurodegeneration: a new X-linked dominant disorder with brain iron accumulation - Hayflick, Susan J.; Kruer, Michael C.; Gregory, Allison; Haack, Tobias B.; Kurian, Manju A.; Houlden, Henry H.; Anderson, James; Boddaert, Nathalie; Sanford, Lynn; Harik, Sami I.; Dandu, Vasuki H.; Nardocci, Nardo; et al. (Brain (London, England : 1878), 2013)
Neurodegenerative disorders with high iron in the basal ganglia encompass an expanding collection of single gene disorders collectively known as neurodegeneration with brain iron accumulation. These disorders can largely be distinguished from one another by their associated clinical and neuroimaging features. The aim of this study was to define the phenotype that is associated with mutations in WDR45, a new causative gene for neurodegeneration with brain iron accumulation located on the X chromosome. The study subjects consisted of WDR45 mutation-positive individuals identified after screening a large international cohort of patients with idiopathic neurodegeneration with brain iron accumulation. Their records were reviewed, including longitudinal clinical, laboratory and imaging data. Twenty-three mutation-positive subjects were identified (20 females). The natural history of their disease was remarkably uniform: global developmental delay in childhood and further regression in early adulthood with progressive dystonia, parkinsonism and dementia. Common early comorbidities included seizures, spasticity and disordered sleep. The symptoms of parkinsonism improved with l-DOPA; however, nearly all patients experienced early motor fluctuations that quickly progressed to disabling dyskinesias, warranting discontinuation of l-DOPA. Brain magnetic resonance imaging showed iron in the substantia nigra and globus pallidus, with a 'halo' of T1 hyperintense signal in the substantia nigra. All patients harboured de novo mutations in WDR45, encoding a beta-propeller protein postulated to play a role in autophagy. Beta-propeller protein-associated neurodegeneration, the only X-linked disorder of neurodegeneration with brain iron accumulation, is associated with de novo mutations in WDR45 and is recognizable by a unique combination of clinical, natural history and neuroimaging features.